Nonlinear Properties of the Gotland Deep – Baltic Sea - GRELOWSKA, Grażyna; KOZACZKA, Eugeniusz (Archives of Acoustics, 2015)
The properties of the nonlinear phenomenon in water, including sea water, have been well known for many decades. The feature of the non homogeneous distribution of the speed of sound along the depth of the sea is very interesting from the physical and technical point of view. It is important especially in the observation of underwater area by means of acoustical method (Grelowska et al., 2013; 2014). The observation of the underwater space has been carried out for more than hundred years. In the second half of the twentieth century we observed very intense trend of development of the measuring methods of underwater sound speed. It was done mainly in the linear sound propagation aspect. At the end of 20th century nonlinear devices were invented. Thus, from this point of view, knowledge on the nonlinear properties of the sea water is the matter of interest. The phenomenon of nonlinear distortion of elastic waves, and the same the efficiency of nonlinear transfer of energy from the primary wave to the higher harmonic components depend on properties of the medium, especially on the material constant known as the nonlinearity parameter $B/A$. The Baltic Sea is a specific reservoir with untypically low salinity and low depth (Grelowska, 2000). In the paper results of investigation of nonlinear properties of the South and the Central Baltic by means of thermodynamic method are presented.